PROFIL AGROINDUSTRI EMPING JAGUNG DI KABUPATEN ACEH UTARA - Zuriani, Zuriani; Martina, Martina (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2023)
Farmers Group Bungong Seulanga is the only producer of corn chips in North Aceh Regency. Since 2018, the agroindustry has not experienced development. This study aims to determine how the constraints, production costs, revenues, profits, business feasibility level, and cost of goods sold. The data used are primary and analysed used descriptive qualitative and quantitative methods. The results showed that the business experienced obstacles related to production techniques, quality of chips, production stock, marketing, packaging, management and business legalization. Agroindustry produces chips as much as 25 kg / month with production costs other than labor wages of Rp. 348,250, -. Agro-industry revenue of Rp. 1,250,000, - and a profit of IDR 901,750. If the labor wage is calculated, the business will suffer losses and it is not feasible because the total cost reaches Rp. 1,948,250. The HPP which benefits the corn chips agroindustry is currently above Rp. 77,930 / kilogram.